Gender Affirming Laryngeal and Voice Surgery - Srivastava, Rakesh (Indian Journal of Plastic Surgery, 2022)
Gender affirmation laryngeal and voice surgeries are components of “voice-lift” or cosmetic voice surgeries. Feminization surgery can modify vocal folds (fundamental frequency [Fo]) and vocal tract (resonance frequency). For increased pitch, vocal folds should be shorter, thinner, and tighter. Cricothyroid approximation (CTA) surgery increases tension of the vocal folds. Endoscopic procedures for pitch raising are done by shortening the length and reducing mass of vocal folds. This shortening is achieved by surgically creating anterior glottic web. Comparing the results of various open and endoscopic surgical techniques, fundamental frequency (Fo) is raised maximally and remains stable after GL as compared with CTA.
Keywords: transgender; phonosurgery